Local Energy: Spatial Proximity of Energy Providers to Their Power Resources - Hoffacker, Madison K.; Hernandez, Rebecca R. (Frontiers in Sustainability, 2020)
Ambitious greenhouse gas emission reduction targets have underscored the need for a rapid global transition to decentralized, renewable, and more local energy systems, but distance between resources and energy providers have not been assessed. Using California as a model system, we quantified and compared the extent to which energy providers — publicly owned utilities (POUs), community choice aggregations (CCAs), and cooperatives (co-ops) — contract resources near their energy demands and evaluated these trends across all energy resource types. We found CCAs, on average procure their pooled energy resources further from their service territories than long-standing POUs and co-ops. Nevertheless, on average, a larger percent of CCA’s energy is from renewable resources compared to POUs and co-ops. In an era where interest in local energy generation is growing, this study reveals energy providers source resources far from demand loads and newer providers may face additional and unique barriers to contracting energy locally.